Biking across America : my coast-to-coast adventure and the people I met along the way - Stutzman, Paul V. (Grand Rapids, MI : Revell, 2013)
After Paul Stutzman finished hiking the Appalachian Trail, he found himself longing for another challenge, another adventure. Trading his hiking boots for a bicycle, Paul set off to discover more of America. Starting at Neah Bay, Washington, and ending at Key West, Florida, Paul traversed the 5,000-mile distance between the two farthest points in the contiguous United States. Along the way he encountered nearly every kind of terrain and weather the country had to offer-as well as hundreds of fascinating people whose stories readers will love. Through cold and heat, loneliness and exhaustion, abundance and kindness, Paul pedaled on. His reward-and the readers'-is a glimpse of a noble yet humble America that still exists and inspires. Anyone who longs for adventure, and who loves travel and stories of travel will enjoy this book.
1. A new story -- 2. Five thousand miles of unknowns -- 3. The road chosen -- 4. The emerald triangle -- 5. Danny -- 6. Caples Lake caper -- 7. Middlegate Station -- 8. The peace train -- 9. Long night in Utah -- 10. Colorful Colorado -- 11. Heroes and friends -- 12. Choices on the road toward home -- 13. Biking the Bible Belt -- 14. Kudzu, cotton fields, and canines -- 15. Front porches and diners -- 16. One way -- 17. It's about time.
Keywords: Stutzman, Paul V. -- Travel -- United States; Bicycle touring -- United States; Bicycle touring; United States